2023
DOI: 10.3390/genes14061180
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Acute Myeloid Leukemia by Cell-Free DNA 5-Hydroxymethylcytosine

Abstract: Epigenetic abnormality is a hallmark of acute myeloid leukemia (AML), and aberrant 5-hydroxymethylcytosine (5hmC) levels are commonly observed in AML patients. As epigenetic subgroups of AML correlate with different clinical outcomes, we investigated whether plasma cell-free DNA (cfDNA) 5hmC could categorize AML patients into subtypes. We profiled the genome-wide landscape of 5hmC in plasma cfDNA from 54 AML patients. Using an unbiased clustering approach, we found that 5hmC levels in genomic regions with a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
(84 reference statements)
0
0
0
Order By: Relevance
“…CfDNA are degraded DNA fragments released into body fluids from both normal and tumor cells in cancer patients. Several studies, including our own, have shown that cfDNA 5hmC is a highly sensitive marker for the early detection of lung cancer and other cancer types [16][17][18][19][20][21][35][36][37][38][39][40][41][42][43][44]. Our group and others also demonstrated that a cfDNA 5hmC signature is significantly associated with patient prognosis in acute myeloid leukemia and pancreatic cancer [19,44].…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…CfDNA are degraded DNA fragments released into body fluids from both normal and tumor cells in cancer patients. Several studies, including our own, have shown that cfDNA 5hmC is a highly sensitive marker for the early detection of lung cancer and other cancer types [16][17][18][19][20][21][35][36][37][38][39][40][41][42][43][44]. Our group and others also demonstrated that a cfDNA 5hmC signature is significantly associated with patient prognosis in acute myeloid leukemia and pancreatic cancer [19,44].…”
Section: Introductionsupporting
confidence: 58%
“…Adjustment of treatment strategies based on prognostic biomarkers has demonstrated improved survival rates in other cancers, such as colon cancer [52]. cfDNA 5hmC markers have demonstrated remarkable versatility across various applications, exhibiting high sensitivity and specificity in pan-cancer detection [16][17][18][19][20][21][35][36][37][38][39][40][41][42][43] and the ability to differentiate cancer types and tissue origins [18,48]. This utility extends to predicting prognosis in various cancers, such as acute myeloid leukemia [19], pancreatic cancer [44], and lung cancer, as demonstrated herein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As 5hmC closely correlates with gene expression [11], it may also serve as a reliable marker for changes in tumor gene expression in response to ICI treatment. Previous studies indicate that cfDNA 5hmC has a high sensitivity for cancer detection and prognosis prediction [30][31][32][33][34][35][36][37][38][39][40][41][42]. We further add to this body of evidence by demonstrating that cfDNA 5hmC can predict the therapeutic response in lung cancer patients receiving ICI therapy.…”
Section: Discussionmentioning
confidence: 74%
“…Using a highly sensitive nano-hmC-Seal method [29], we and others have demonstrated that 5hmC signatures in plasma cfDNA are highly sensitive for the early detection and prognosis of diverse cancers, including lung cancer [30][31][32][33][34][35][36][37][38][39][40][41][42]. However, the predictive value of cfDNA 5hmC in lung cancer immunotherapy response prediction remains unexplored.…”
Section: Introductionmentioning
confidence: 99%